The methods and instruments of influence of self-governing authorities on the activation of industrial production of the city - Nataliya Holub (Cхід, 2014)
The possibilities of self-governing authorities to create necessary conditions for development of industrial production in the city were analyzed by author in this article. It was established that the role of self-governing authorities involves the possibility to concretize the methods, means and mechanisms of goal achievement which are determined within the frame of national industrial politics and also to attach them to the peculiarities of different administrative-territorial entities and to take into account the specificity of demographic, resource, ecological and others characteristics. The article includes the dependence between the territorial dynamics of development and branch one. It was proved that only local authority of big cities the industrial centers of country can act as party of Ukrainian industrial politics in modern business environment. The positive experience of managerial cooperation between industrial enterprises of the city and local authorities was investigated. In conclusion it was said that the advantages for self-governing authorities of industrial type of the organization of subnational entity consist in that fact that this type significantly simplifies search and realization of developmental variation. Firstly, it has wide guaranty support from the part of state government, secondly, the profit from the side of attraction possibility of investment and other financial resources to the economy of industrial cities is provided. With the purpose to activate the development of industrial production on the concrete territory there is a range of efficient methods and instruments of influence for self-governing authorities. The main from them are: execution of an examination of investment projects; advertisement of local manufacturers; providing of budgetary credits, guaranties and assurances, sale or lend-lease of objects of communal properties; formation of strategy of internal self-development and strategy of attraction of external resources.